Decision Support System Determination Of Employees Receiving Bonus Using The Weighted Product Method - Pandi Barita Nauli Simangunsong (Sean Institute, 2020)
Decision support systems are part of computer-based information systems including knowledge-based systems or knowledge management that are used to support decision making in an organization or company. It can also be said as a computer system that processes data into information for making decisions on specific semi-structured problems. The Wighted Product method is part of the Fuzzy Multi Attribute Decision Making (FMADM) concept where normalization is required in the calculation. The Weighted Product method is expected to be able to develop a decision support system software that can be used by an agency, which will be an alternative choice and give a weighted value to the comparison of alternatives and their criteria, while the criteria are discipline, responsibility, loyalty and quality of work. The criteria have been determined by the company. The results showed that the use of the Weighted Product as a decision support system model for determining employee bonus recipients at UD. Rama Jaya Trading can assist company owners in determining which employees are entitled to be recommended to receive multi-criteria weighting bonuses and selection more quickly, carefully and more effectively.